2005
DOI: 10.1107/s1600536805025833
|View full text |Cite
|
Sign up to set email alerts
|

DiethylN,N′-cyclohexane-1,4-diyldioxalamate

Abstract: Key indicatorsSingle-crystal X-ray study T = 100 K Mean (C-C) = 0.004 Å R factor = 0.073 wR factor = 0.177 Data-to-parameter ratio = 15.3 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We were able to observe that the pendant arm of oxalamate 1 displayed a triplet for methyl protons and a highly symmetric 14 lines multiplet for the methylene protons, in contrast to the quartet triplet multiplicity reported by Albano and co-workers 10 and for the analog oxalamate derived from trans-1,4-diaminocyclohexane. 9 In our case, the multiplicity of methylene protons indicates that they have a different chemical environment, probably as a result of slow or no rotation of the pendant arm. The same behavior was observed for compound 2 and is equally expected for 3-6 because they gave broad signals.…”
Section: Nmr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to observe that the pendant arm of oxalamate 1 displayed a triplet for methyl protons and a highly symmetric 14 lines multiplet for the methylene protons, in contrast to the quartet triplet multiplicity reported by Albano and co-workers 10 and for the analog oxalamate derived from trans-1,4-diaminocyclohexane. 9 In our case, the multiplicity of methylene protons indicates that they have a different chemical environment, probably as a result of slow or no rotation of the pendant arm. The same behavior was observed for compound 2 and is equally expected for 3-6 because they gave broad signals.…”
Section: Nmr Analysismentioning
confidence: 99%
“…9 Oxalamate 1 was first prepared by Albano and co-workers from enantiopure (R,R)-and (S,S)-trans-1,2-diaminocyclohexane. 10 Spectroscopic data for oxalamate 1 determined in this study are similar to those reported by Albano, however we observed a melting point of 180-182°C which is 15 ºC higher than that reported.…”
Section: Synthesismentioning
confidence: 99%